Corticosteroid Effects in IgA Nephropathy by Baseline Proteinuria and Estimated GFR - Dana Kim; Brendon L. Neuen; Jicheng Lv; Michelle A. Hladunewich; Vivekanand Jha; Lai Seong Hooi; Helen Monaghan; Robert A. Fletcher; Laurent Billot; Vlado Perkovic; Hong Zhang; Muh Geot Wong; et al. (Kidney International Reports)
Introduction: Higher proteinuria and lower estimated glomerular filtration rate (eGFR) are predictors of kidney failure in IgA nephropathy (IgAN); however, it is uncertain whether these markers modify response to corticosteroids. This post hoc analysis of the TESTING trial assessed the effects of methylprednisolone on kidney and safety outcomes by baseline proteinuria and eGFR. Methods: A total of 503 participants with IgAN and proteinuria ≥ 1 g/d were randomized to oral methylprednisolone (full-dose 0.6–0.8 mg/kg/d or reduced-dose 0.4 mg/kg/d) versus placebo. Participants were categorized according to baseline proteinuria (1–< 1.5, 1.5–< 3, ≥ 3 g/d) and eGFR (20–< 30, 30–< 45, 45–< 60, 60–120 ml/min per 1.73 m2). Results: Over a mean follow-up of 4.2 years, methylprednisolone lowered the risk of the primary outcome (≥ 40% decline in eGFR, kidney failure, or death because of kidney disease) by 47% (hazard ratio: 0.53, 95% confidence interval [CI]: 0.39–0.72), with consistent effects regardless of baseline proteinuria (P-interaction = 0.53) or eGFR (P-interaction = 0.68). Similarly, methylprednisolone improved the decline in total eGFR slope and reduced proteinuria, regardless of baseline proteinuria or eGFR (all P-interaction > 0.10). The number of serious adverse events (SAEs) was higher with methylprednisolone than with placebo across all proteinuria and eGFR levels. Absolute benefits and harms varied by eGFR, such that for those with eGFR < 30 ml/min per 1.73 m2, absolute risk of SAEs may outweigh potential advantages. However, this subgroup was small, predominantly received full-dose methylprednisolone, and was older than those with eGFR ≥ 30 ml/min per 1.73 m2. Conclusion: Methylprednisolone improves kidney outcomes in IgAN at high risk of progression, irrespective of proteinuria or eGFR, although the risk-benefit balance may be less favorable in those with advanced disease plus other risk factors for corticosteroid-related toxicities.